2002
DOI: 10.1001/archsurg.137.9.1008
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Symptoms and Failure After Antireflux Surgery

Abstract: Background: Outcomes in patients having surgery for gastroesophageal reflux disease are most commonly determined by symptomatic assessment. Objective testing is usually reserved for symptomatic patients. Hypothesis: To evaluate the relationship between symptomatic and objective outcomes after antireflux surgery. Design: Retrospective analysis of prospectively collected data. Setting: A tertiary care teaching hospital with a comprehensive esophageal physiology laboratory. Interventions: A 360°(Nissen) fundoplic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
1

Year Published

2003
2003
2011
2011

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(52 citation statements)
references
References 18 publications
3
48
1
Order By: Relevance
“…This suggests that the poor outcome in these patients is unlikely due to persistent acid reflux. This supports the findings of Khajanchee et al [12], who found a poor correlation between postoperative reflux symptoms and actual reflux as judged by pH testing.…”
Section: Discussionsupporting
confidence: 91%
“…This suggests that the poor outcome in these patients is unlikely due to persistent acid reflux. This supports the findings of Khajanchee et al [12], who found a poor correlation between postoperative reflux symptoms and actual reflux as judged by pH testing.…”
Section: Discussionsupporting
confidence: 91%
“…These tests have resource implications and radiological exposure risk. On the other hand, there is poor correlation between postoperative symptoms and definite reflux [2]. There is no consensus on the question of how to treat asymptomatic patients who have mechanical failure of the antireflux surgery and the present study did not answer it.…”
Section: Dear Sircontrasting
confidence: 74%
“…However, as we have shown before, there is little overlap between subjective-and objective-failure patient groups. 7 If we were to include the 11 patients with abnormal 24-hour pH study results who were completely asymptomatic, our absolute success rate would decrease to about 67%. However, 5 of these 11 asymptomatic patients had a Collis gastroplasty and should not be counted, as we have shown previously that it is gastric mucosa within the neoesophagus that causes abnormal pH test results in these patients and not gastroesophageal reflux.…”
Section: Outcomes Of Laparoscopic Reoperation For Failed Arsmentioning
confidence: 99%
“…Symptom assessment was performed using a standardized assessment tool that grades reflux, heartburn, and dysphagia on a scale of 0 to 4, with higher ordinal values representing greater frequency or severity of symptoms. 7 Routine preoperative evaluation included esophageal manometry, 24-hour pH testing, and upper endoscopy. Upper gastrointestinal tract contrast radiography and/or a radionuclide gastric emptying study was ordered if indicated by the patient's symptoms or to clarify anatomy.…”
Section: Outcome Measuresmentioning
confidence: 99%